Peritoneal dialysis related peritonitis due to Mycobacterium spp.: A case report and review of literature - Anusha Rohit; Georgi Abraham (Springer, 2019)
Mycobacterium tuberculous peritonitis is a less common cause of peritoneal dialysis related infection in developed countries. As both CAPD and APD are being used as renal replacement therapy in developing countries of South Asia, Mycobacterium tuberculous peritonitis are being reported. Any culture negative peritonitis should be investigated for this entity. In this manuscript, we report an index case and our experience with literature review of Mycobacterium tuberculous peritonitis. The diagnostic techniques, management and outcome are described.